Intrinsic Motivation Linked to Early Writing Skills in Second Graders: Motivasi Intrinsik Terkait dengan Kemampuan Menulis Awal pada Siswa Kelas Dua - Mariza Istifarania (Academia Open, 2025)
General Background Writing skills constitute a foundational component of literacy development in early elementary education and are closely associated with students’ overall academic progress. Specific Background At ages 7–8, children are in the concrete operational stage, during which logical thinking and basic writing abilities develop rapidly, yet many second-grade students still experience difficulties in handwriting, sentence construction, and written expression. Knowledge Gap Despite the recognized importance of motivation in learning, limited qualitative evidence explains how intrinsic motivation relates specifically to early writing performance in lower-grade elementary students. Aims This study aims to analyze learning motivation from the perspective of writing skills among second-grade students at SDN Sumput Sidoarjo. Results Using a qualitative case study with observations, interviews, and documentation triangulated descriptively, findings indicate that students with high intrinsic motivation demonstrate more fluent, neat, and consistent writing, whereas those with low motivation struggle with letter formation, organization, punctuation, capitalization, and idea development. Novelty The study provides an in-depth, contextual description linking intrinsic motivational characteristics—interest, desire, and independence—to specific mechanical and compositional aspects of early writing. Implications These findings suggest that teachers and parents should cultivate students’ interest and autonomy in writing activities to support foundational literacy development in primary education. Highlights: Learners with stronger internal drive produced smoother and more orderly handwriting. Mechanical errors such as spacing, punctuation, and capitalization remained common among less engaged pupils. Idea expansion was limited, with most children producing only short, simple sentences. Keywords: Intrinsic Motivation; Writing Skills; Early Literacy; Elementary Education; Qualitative Case Study